The Right to Private Life under the ECHR with Special Regard to Central Europe - Wedeł-Domaradzka , Agnieszka (The ECHR at 70: The Central European Narrative, 2025)
This study addresses the right to private life in the jurisprudence of the European Court of Human Rights. The right to private life will be presented in the context of this right’s general scope. The study will also analyse how the content and scope of the right to private life has been shaped in the jurisprudence regarding the content of the European Convention for the Protection of Human Rights and Fundamental Freedoms. The jurisprudence of the Strasbourg Court has also shaped the very content and understanding of the right to private life. Thus, those judgments and those parts that affect the understanding of the right to private life will be presented. The most extensive consideration will be given to judgments rendered in cases concerning the observance of the right to private life in Central European countries. The consideration will cover three spheres of private life: the physical, psychological or moral integrity of individuals, privacy and the protection of personal autonomy and identity. The analysis will provide conclusions. These will include two aspects: an indication of what is specific to violations of the right to privacy in Central European countries and identifying the challenges posed to these countries. The latter aspect is based on already existing cases in Western Europe.Keywords: right to private life, human rights, European Convention for the Protectionof Human Rights and Fundamental Freedoms, European Court of HumanRights, Central Europe, autonomy, privacy, identity